Employee’s Performance in Small and Medium Enterprises: A Human Resource Management Critical Analysis - Lubon, Cliff Kirl (JPAIR Multidisciplinary Research, 2021)
Performance management is an important step in the organization’s human resource management because it hones and improves employee performance. Determining the extent of functional flexibility in human resource management, organizational communication, leadership behaviors, and employee performance, including their significant relationship, as well as the significant effects, is the aim of this study. A descriptive survey and correlational research design were utilized to gather the said information through a questionnaire with 498 respondents. It was revealed through weighted mean, Pearson correlation, and multiple linear regression analysis that there was a significant low positive correlation between functional flexibility in human resource management and employee performance, organizational communication and employee performance, transformational leadership behaviors and employee performance, and transactional leadership behaviors with employee performance. Given the overall results, the study concluded that all four (4) independent variables had significant effects on employee performance in Small and Medium Enterprises.